2010
DOI: 10.1177/039463201002300203
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Therapy in Children: Overview and Challenges

Abstract: Helicobacter pylori is one of the most common infections found in humans. It was first identified in 1982 and by 1989 had been associated with gastric inflammation and ulcers in adults and children. During the 1990's evidence emerged of its etiologic role in stomach cancers in adults. That the infection is common and may have serious consequences, has led to an avalanche of research during the last twenty years. During this time, there have been many studies on children which have sought an effective and safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Epidemiological studies have demonstrated that the prevalence of H. pylori infection increases with advancing age and is higher in developing countries and among population with low socioeconomic background, probably due to conditions that favor the acquisition of infection, such as poor hygiene, crowded living conditions and absence or deficiency of sanitation [20]. It has been reported that in developing countries, H. pylori infection is usually acquired before 10 years of age and in the absence of antibiotic therapy, it generally persists for life [21].…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that the prevalence of H. pylori infection increases with advancing age and is higher in developing countries and among population with low socioeconomic background, probably due to conditions that favor the acquisition of infection, such as poor hygiene, crowded living conditions and absence or deficiency of sanitation [20]. It has been reported that in developing countries, H. pylori infection is usually acquired before 10 years of age and in the absence of antibiotic therapy, it generally persists for life [21].…”
Section: Resultsmentioning
confidence: 99%
“…Few randomized, placebo-controlled treatment trials are available in children for the different outcomes (gastritis or peptic ulcer), and often consist of only small numbers of cases [86,106]. Clearly in children as in adults, successful eradication of H. pylori markedly reduces the risk of ulcer recurrence [107][108][109][110]. Thus, there is general consensus worldwide to treat H. pylori infection when there is endoscopic evidence of peptic ulceration.…”
Section: Nevertheless Specific Populations Such As Immigrants and Rumentioning
confidence: 99%
“…Nonetheless, twice daily PPI therapy has been the rule in most pediatric efficacy studies for H. pylori eradication [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Although extending PPI dose timing may be attractive to some investigators, this PPI schedule may challenge the child’s and adolescent’s adherence to the medication [4], which may be important in determining clinical outcomes.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Over the last two decades, there have been many studies on children which have sought an effective and safe treatment to eradicate the infection, but as yet, no therapy regimen has been found which is always effective and safe [4]. Differences in drug response among pediatric patients are common [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation